Acute disseminated encephalomyelitis after allogeneic bone marrow transplantation for pure red cell aplasia – A case report and review of the literature. (6th December 2012) - Paisiou, Anna; Goussetis, Evgenios; Dimopoulou, Maria; Kitra, Vassiliki; Peristeri, Ioulia; Vessalas, Giorgos; Gavra, Maria; Theodorou, Virginia A.; Graphakos, Stelios
Abstract ADEM is a rare inflammatory demyelinating disease of the CNS, which usually presents after a viral infection or a vaccination. We report a 15‐yr‐old boy who was diagnosed with ADEM after an HLA‐identical sibling allogeneic BMT for transfusion‐dependent PRCA. His course was complicated with GVHD affecting the skin and lungs. Five months post‐BMT, he developed neurological symptoms including sudden mental status alteration, dysarthria, facial nerve palsy, and acute paraplegia. The MRI revealed multifocal hyperintense lesions mainly in the subcortical white matter of the cerebrum, the brainstem, the basal ganglia, and the thalami. CSF examination was normal. There was no laboratory evidence of infection. The typical MRI findings and an acute monophasic clinical course were consistent with the diagnosis of ADEM. Clinical and radiological improvement was observed after treatment with high‐dose steroids and IVIG. Complete neurologic recovery was achieved six months after the onset of symptoms. We present a rare case of ADEM post‐BMT and review of the literature.